Challenges in Nursing Education in the New Normal: Basis for Faculty Enhancement Program - Edmelyn B. Cacayan; Ma. Elizabeth C. Baua; Angelito Estoesta Alvarado (Humanistic Network for Science and Technology (HNST), 2020)
Education s vital to every Filipino especially the delivery of quality education without compromising the health and safety of the students amidst COVID 19 pandemic. With the current global health crisis and government pronouncements prohibiting the conduct of face-to-face classes both in basic education (DepEd) and Higher education (CHED). Isabela State University has decided to roll out and launched its new approach, called telEducation. It has ramped up its efforts in fully implementing flexible remote learning for its students to ease its transition to what might become the new normal for educational institutions. This study utilized a descriptive survey method of investigation to secure adequate and reliable data. The researcher used this design to gather necessary data, assess and determine the challenges facing nursing education in the new normal by the nursing faculty of Isabela State University, College of Nursing. The questionnaires were floated through the use of google forms as a platform. The respondents who participated in this study were 15 nursing faculty comprises of 7 permanent as core faculty and 8 instructors under a contract of service. This study concluded that inadequate instructor training for new normal education; limited time for the preparation of modules, exams, and other related to instruction is due to the limited time of the university administrators or concern authorities to conduct since the summer class has already implemented. The said interventions made it more difficult to conduct due to the implementing community quarantines. Furthermore, there are numerous nursing-related experiences/activities but limited time for implementation; Students find it difficult to comprehend some activities due to the absence of physical contact of the instructor/s; faculty experiencing physical problems (eg. eye strain and frontal headache) due to long hours of exposure on computer monitor or gadgets are noted concerns in relation to the delivery of instructions. Keywords: nursing education; new normal; challenges